Investigating the effect of LRP/LR down-regulation on malignant melanoma cells and assessing the effect of LRP/LR antibodies on metastatic malignant melanoma mouse models - Rebelo, Thalia Martins (My University, 2017)
On a cellular level cancer is described as abnormal cellular growth resulting from uncontrolled cellular proliferation and reduced apoptosis. Cancer is seen as a non-discriminative disease, therefore exhibiting high incidence and mortality rates. Additionally, cancer is classified as a global burden in both economically developed and developing countries. The 37kDa/67kDa laminin receptor (LRP/LR) is seen to be over-expressed in tumor cells when compared to their normal cell counterparts. This receptor has been implicated in several tumourigenic processes such as cell migration and adhesion but importantly for the present study, the maintenance of cellular viability and the evasion of apoptosis. The aim of the present study was to investigate the role of LRP/LR on the cellular viability of early (A375) and late stage (A375SM) malignant melanoma cells. Flow cytometry revealed that both malignant melanoma cell lines exhibit high cell surface LRP/LR levels and with further analysis using median fluorescence intensity, it was observed that A375SM cells contain approximately 86% more cell-surface LRP/LR than A375 cells. In addition, western blotting and densitometric analysis suggested that A375SM cells contain 60% more total LRP/LR levels than A375 cells. Furthermore, western blot analysis revealed that targeting the mRNA of the 37kDa LRP using a LRP-specific siRNA (Dharmacon ON-TARGET Human RPSA) in A375 and A375SM cells led to significant down-regulation of 77% and 72% in LRP expression, respectively. Consequently, MTT assays showed that LRP down-regulation led to significant reductions of 47% and 61% in the viability of A375 and A375SM cells, respectively. An alternative LRP-specific siRNA (Mission esiRNA-RPSA) was used in order to confirm specificity and to exclude any off-target effects of Dharmacon ONTARGET Human RPSA for LRP. Confocal microscopy with the addition of the Airyscan processing tool indicated nuclear morphological changes suggestive of apoptotic induction in the form of cell death occurring in both malignant melanoma cell lines post LRP down-regulation. Annexin-V/PI assays confirmed this observation, by revealing that A375 and A375SM cells underwent apoptotic induction post LRP down-regulation in comparison to the untreated cells. Additionally, caspase-3 activity assays revealed that both cell lines experienced apoptotic induction after siRNA-mediated down-regulation of LRP. Caspase-8 and -9 activity assays suggested that post LRP down-regulation; A375 cells undergo apoptosis solely via the extrinsic pathway, while A375SM cells are thought to undergo apoptosis via the intrinsic pathway. According to Munien et al, 2017 [137], application of the anti-LRP/LR specific antibody IgG1 iS18 has led to a significant reduction in metastatic potential of A375 and A375SM malignant melanoma cells in vitro. Therefore the aim of the present in vivo study was to further investigate the significance of blocking LRP/LR with the IgG1-iS18 antibody and how this will be effective in the treatment of malignant melanoma in vivo using a MF-1 nude mice model. The mice were divided into three groups; with three mice each. This was followed by treatment of group 1 with 0.885mg/ml of the IgG1-iS18 antibody intraperitoneally, twice a week, group 2 was administered with the Phosphate Buffered Saline (PBS) vehicle control solution and the last group remained untreated. The results of this pilot study indicated that three of the nine mice developed external tumour formation; one of the mice being from the untreated group with a tumour volume larger than the other two mice which were from the IgG1-iS18 treatment group. When comparing the tumour formation between the untreated and treated group, there was a large reduction in tumour weight and volume. To conclude, LRP/LR plays a critical role in the maintenance of tumor cellular viability and metastasis, recommending this receptor as a promising therapeutic target and proposing the potential use of siRNA technology as well as the IgG1-iSi8 antibody for the treatment of malignant melanoma.
A research report submitted to the faculty of Science, University of the Witwatersrand, Johannesburg, in the fulfilment of the requirements for the degree of Masters of Science, 2017
Keywords: Cancer; Amyloid beta-protein; Esophagus--Cancer